2020
DOI: 10.1123/jab.2020-0040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Increased Lumbar Lordosis on Lumbar Multifidus and Longissimus Thoracis Activation During Quadruped Exercise in Patients With Chronic Low Back Pain: An EMG Study

Abstract: The objective was to investigate the electromyographic activity of the lumbar multifidus (MF) muscle and longissimus thoracis muscle, along with their activity ratio (MF longissimus thoracis ratio), during quadruped stabilization exercise performed with neutral posture and with increased lumbar lordosis in patients with chronic low back pain (CLBP). A total of 23 patients with CLBP (12 females and 11 males) were recruited based on inclusion and exclusion criterion. Each patient performed 4 exercises in random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…The increased activity in painful side LM may be in response to the perception of pain in multifidus. 16,17 The results of previous studies with the comparison of symptomatic and symptomatic individuals with CLBP and with the comparison of painful and nonpainful sides are the same as current study elaborating the higher muscle contraction in CLBP than control. 17,18 However, contrary to this another study found no significant difference between non-painful and painful individuals with CLBP 19 .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The increased activity in painful side LM may be in response to the perception of pain in multifidus. 16,17 The results of previous studies with the comparison of symptomatic and symptomatic individuals with CLBP and with the comparison of painful and nonpainful sides are the same as current study elaborating the higher muscle contraction in CLBP than control. 17,18 However, contrary to this another study found no significant difference between non-painful and painful individuals with CLBP 19 .…”
Section: Discussionsupporting
confidence: 65%
“…16,17 The results of previous studies with the comparison of symptomatic and symptomatic individuals with CLBP and with the comparison of painful and nonpainful sides are the same as current study elaborating the higher muscle contraction in CLBP than control. 17,18 However, contrary to this another study found no significant difference between non-painful and painful individuals with CLBP 19 . These differences in results may be due to differences in movement during the measurement of %MVC.…”
Section: Discussionsupporting
confidence: 65%
“…In addition, NET can increase joint stability by improving proprioception to control joint alignment [19,45,46]. When TLJ rotation occurs, a neutral position is maintained by stabilizers and rotators, such as the LD, multifidus, and SPI [47]. This is consistent with the fact that if taping is applied parallel to the muscle fibers, it can facilitate muscle function [16][17][18].…”
Section: Discussionmentioning
confidence: 78%
“…Pain increases muscle tone, which then aggravates pain, leading to improper postural control ( Roland, 1986 ; Lo et al, 2019 ). Although there are many methods for treating CLBP ( Rubinstein et al, 2011 ; Haładaj and Topol, 2016 ), selection of appropriate intervention measures and their effects should be clinically assessed ( Kravitz et al, 1981 ; Shah et al, 2020 ). Manual palpation is often used for clinical evaluation of musculoskeletal diseases, such as lower back muscles and spine ( Abbott et al, 2009 ; Masaki et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%